Analisis Profitabilitas, Ukuran Perusahaan, Leverage dan Pengaruhnya Terhadap Manajemen Laba Pada Sektor Transportasi dan Logistik - Heny Septina, Rika; Triono, Hermawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the effect of profitability, company size, and leverage on earnings management practices among issuers in the transportation and logistics sector on the Indonesia Stock Exchange. This study uses a quantitative approach, analyzing secondary data from financial reports for the 2021-2024 period, selected through purposive sampling techniques. The data was then processed using multiple linear regression. The findings show that profitability has no impact on earnings management. Conversely, company size was found to have a significant negative effect, while leverage has a significant effect on earnings management practices. Theoretically, these results indicate that large company size encourages stricter supervision, thereby minimizing profit manipulation. However, high debt burdens actually trigger management to engage in profit management in order to meet financial obligations. Simultaneously, these three variables contribute 25% to the variation in profit management, while the remaining 75% is influenced by other external factors outside the research model. This study is expected to enrich the literature on profit management practices in public companies.